2003
DOI: 10.1038/sj.cdd.4401341
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle molecules and vertebrate neuron death: E2F at the hub

Abstract: Vertebrate neuron cell death is both a normal developmental process and the catastrophic outcome of nervous system trauma or degenerative disorders. Although the mechanisms of such death include an evolutionarily conserved core apoptotic pathway that is highly homologous to that first described by Horvitz and co-workers in Caenorhabditis elegans, it appears that many instances of neuron death additionally require the transcription-dependent induction of proapoptotic molecules. One such proapoptotic transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 125 publications
4
95
0
Order By: Relevance
“…Although it appears that they face continuing stress to re-enter the cell cycle, a series of anti-growth factors prevent them from normally doing so (Copani and Nicoletti, 2005). A growing number of in vivo and in vitro studies, however, show that post-mitotic neurons can re-enter the cell cycle after brain injury in rat and humans (Hayashi et al, 2000, Copani et al, 2001, Love, 2003, Becker and Bonni, 2004, Greene et al, 2004, Herrup et al, 2004, Kuan et al, 2004, Di Giovanni et al, 2005, Copani et al, 1999, Liu and Greene, 2001, Rao et al, 2007. This cell cycle re-entry is a critical element of the DNA damage response of post mitotic neurons leading to apoptosis (Kruman et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although it appears that they face continuing stress to re-enter the cell cycle, a series of anti-growth factors prevent them from normally doing so (Copani and Nicoletti, 2005). A growing number of in vivo and in vitro studies, however, show that post-mitotic neurons can re-enter the cell cycle after brain injury in rat and humans (Hayashi et al, 2000, Copani et al, 2001, Love, 2003, Becker and Bonni, 2004, Greene et al, 2004, Herrup et al, 2004, Kuan et al, 2004, Di Giovanni et al, 2005, Copani et al, 1999, Liu and Greene, 2001, Rao et al, 2007. This cell cycle re-entry is a critical element of the DNA damage response of post mitotic neurons leading to apoptosis (Kruman et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These include the retinoblastoma-deficient mouse (Clarke et al, 1992;Jacks et al, 1992;Lee et al, 1992), cerebellar targetrelated cell death (Herrup and Busser, 1995), oncogene expression in maturing neurons (Feddersen et al, 1992), oxidative stress as suggested by the harlequin mouse (Klein et al, 2002), as well as models of stroke (Katchanov et al, 2001) and the superoxide dismutase-1 mouse model of amyotrophic lateral sclerosis (Ranganathan et al, 2001;Ranganathan and Bowser, 2003). The weight of this in vivo evidence, combined with elegant studies in cell culture (Farinelli and Greene, 1996;Giovanni et al, 1999;Greene et al, 2004) strongly implicates the initiation of cell cycling as a causative factor in the death of these neurons. A recent addition to this correlation between neuronal CCEs and cell death is the demonstration by our laboratory that in the mouse model of ataxia-telangiectasia (atm ÏȘ/ÏȘ ), Purkinje cells and striatal neurons also initiate a cell-cycle-like process (Yang and Herrup, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Many cell cycle-regulatory proteins are upregulated during apoptosis of postmitotic neurons in a variety of developmental and pathological circumstances (Becker and Bonni, 2004;Greene et al, 2004;Herrup et al, 2004). Cyclin D1 is one of the best characterized cell cycle-regulatory proteins involved in neuronal apoptosis.…”
Section: Both Cdc2 Expression and Apoptosis Are Increased In Necdindementioning
confidence: 99%
“…These transcription factors contribute to the proliferation of neural stem cells and death of postmitotic neurons (Yoshikawa, 2000;Greene et al, 2004). The proapoptotic E2F member E2F1 is controlled by the retinoblastoma (Rb) protein, which is normally hypophosphorylated in quiescent cells and hyperphosphorylated during cell cycle progression to release active E2F1 (Weinberg, 1995;Nevins, 2001).…”
Section: Introductionmentioning
confidence: 99%